Neutron scattering study of commensurate magnetic ordering in single crystal CeSb2. (6th July 2020) - Liu, Benqiong; Wang, Liming; Radelytskyi, Igor; Zhang, Yun; Meven, Martin; Deng, Hao; Zhu, Fengfeng; Su, Yixi; Zhu, Xiegang; Tan, Shiyong; Schneidewind, Astrid
Abstract: Temperature and field-dependent magnetization M ( T, H  ) measurements and neutron scattering study of a single crystal CeSb2 are presented. Several anomalies in magnetization curves have been confirmed, i.e., at 15.6 K, 12 K, and 9.8 K, respectively. These three transitions are all metamagnetic transitions, which shift to lower temperatures as the magnetic field increases. In contrast to the previous studies that the anomaly at 15.6 K has been suggested as paramagnetic to ferromagnetic phase transition, in our measurement no hysteresis loop around zero field with either H ∥ c or H  ⊥  c has been observed. The anomaly located at around 12 K is antiferromagnetic-like transition, and this turning point will clearly split into two when the magnetic field H ⩾ 2 kOe. A neutron scattering study reveals that the low temperature ground state of CeSb2 orders magnetically with commensurate propagation wave vectors k = (−1, ±1/6, 0) and k = (±1/6, −1, 0), with phase transition temperature T C ∼ 9.8 K.